On local linearization method for stochastic differential equations driven by fractional Brownian motion. Issue 1 (2nd January 2021) - Araya, Héctor; León, Jorge A.; Torres, Soledad
Abstract: We propose a local linearization scheme to approximate the solutions of non-autonomous stochastic differential equations driven by fractional Brownian motion with Hurst parameter 1 / 2 < H < 1 . Toward this end, we approximate the drift and diffusion terms by means of a first-order Taylor expansion. This becomes the original equation into a local fractional linear stochastic differential equation, whose solution can be figured out explicitly. As in the Brownian motion case (i.e., H  = 1/2), the rate of convergence, in our case, is twice the one of the Euler scheme. Numerical examples are given to demonstrate the performance of the method.